Signaling Competition and Social Welfare - Polevoy, Gleb; Smorodinsky, Rann; Tennenholtz, Moshe (ACM Trans. Econ. Comput.)
Keywords: Competition; efficiency; equilibrium; market; social welfare

Multi-Algorithmen-Rendering: Darstellung heterogener 3-D-Szenen in Echtzeit - Petring, Ralf

Budget-restricted utility games with ordered strategic decisions - Drees, Maximilian; Riechers, Sören; Skopalik, Alexander (Proceedings of the 7th International Symposium on Algorithmic Game Theory (SAGT))
We introduce the concept of budget games. Players choose a set of tasks and each task has a certain demand on every resource in the game. Each resource has a budget. If the budget is not enough to satisfy the sum of all demands, it has to be shared between the tasks. We study strategic budget games, where the budget is shared proportionally. We also consider a variant in which the order of the strategic decisions influences the distribution of the budgets. The complexity of the optimal solution as well as existence, complexity and quality of equilibria are analysed. Finally, we show that the time an ordered budget game needs to convergence towards an equilibrium may be exponential.

Brief Announcement: A Model for Multilevel Network Games - Abshoff, Sebastian; Cord-Landwehr, Andreas; Jung, Daniel; Skopalik, Alexander (Proceedings of the 7th International Symposium on Algorithmic Game Theory (SAGT))
Today's networks, like the Internet, do not consist of one but a mixture of several interconnected networks. Each has individual qualities and hence the performance of a network node results from the networks' interplay.We introduce a new game theoretic model capturing the interplay between a high-speed backbone network and a low-speed general purpose network. In our model, n nodes are connected by a static network and each node can decide individually to become a gateway node. A gateway node pays a fixed price for its connection to the high-speed network, but can utilize the high-speed network to gain communication distance 0 to all other gateways. Communication distances in the low-speed network are given by the hop distances. The effective communication distance between any two nodes then is given by the shortest path, which is possibly improved by using gateways as shortcuts.Every node v has the objective to minimize its communication costs, given by the sum (SUM-game) or maximum (MAX-game) of the effective communication distances from v to all other nodes plus a fixed price α > 0, if it decides to be a gateway. For both games and different ranges of α, we study the existence of equilibria, the price of anarchy, and convergence properties of best-response dynamics.

Bounding the Potential Function in Congestion Games and Approximate Pure Nash Equilibria - Feldotto, Matthias; Gairing, Martin; Skopalik, Alexander (Proceedings of the 10th International Conference on Web and Internet Economics (WINE))
In this paper we study the potential function in congestion games. We consider both games with non-decreasing cost functions as well as games with non-increasing utility functions. We show that the value of the potential function $Φ(\sf s)$ of any outcome $\sf s$ of a congestion game approximates the optimum potential value $Φ(\sf s^*)$ by a factor $Ψ_{\mathcal{F}}$ which only depends on the set of cost/utility functions $\mathcal{F}$, and an additive term which is bounded by the sum of the total possible improvements of the players in the outcome $\sf s$. The significance of this result is twofold. On the one hand it provides Price-of-Anarchy-like results with respect to the potential function. On the other hand, we show that these approximations can be used to compute $(1+ε)·Ψ_{\mathcal{F}}$-approximate pure Nash equilibria for congestion games with non-decreasing cost functions. For the special case of polynomial cost functions, this significantly improves the guarantees from Caragiannis et al. [FOCS 2011]. Moreover, our machinery provides the first guarantees for general latency functions.

Approximate pure Nash equilibria in weighted congestion games - Hansknecht, Christoph; Klimm, Max; Skopalik, Alexander (Proceedings of the 17th. International Workshop on Approximation Algorithms for Combinatorial Optimization Problems (APPROX))
We study the existence of approximate pure Nash equilibria in weighted congestion games and develop techniques to obtain approximate potential functions that prove the existence of alpha-approximate pure Nash equilibria and the convergence of alpha-improvement steps. Specifically, we show how to obtain upper bounds for approximation factor alpha for a given class of cost functions. For example for concave cost functions the factor is at most 3/2, for quadratic cost functions it is at most 4/3, and for polynomial cost functions of maximal degree d it is at at most d + 1. For games with two players we obtain tight bounds which are as small as for example 1.054 in the case of quadratic cost functions.

Approximate pure Nash equilibria in Social Context Congestion Games - Gairing, Martin; Kotsialou, Grammateia; Skopalik, Alexander (Proceedings of the 10th International Conference on Web and Internet Economics (WINE))
We study the existence of approximate pure Nash equilibriain social context congestion games. For any given set of allowed costfunctions F, we provide a threshold value μ(F), and show that for theclass of social context congestion games with cost functions from F, α-Nash dynamics are guaranteed to converge to α-approximate pure Nashequilibrium if and only if α > μ(F).Interestingly, μ(F) is related and always upper bounded by Roughgarden’sanarchy value [19].

Algorithmic Aspects of Resource Management in the Cloud - Kniesburges, Sebastian; Markarian, Christine; Meyer auf der Heide, Friedhelm; Scheideler, Christian (Proceedings of the 21st International Colloquium on Structural Information and Communication Complexity (SIROCCO))
In this survey article, we discuss two algorithmic research areas that emerge from problems that arise when resources are offered in the cloud. The first area, online leasing, captures problems arising from the fact that resources in the cloud are not bought, but leased by cloud vendors. The second area, Distributed Storage Systems, deals with problems arising from so-called cloud federations, i.e., when several cloud providers are needed to fulfill a given task.

A Simulation Framework for Analyzing Complex Infinitely Repeated Games - Feldotto, Matthias; Skopalik, Alexander (Proceedings of the 4th International Conference on Simulation and Modeling Methodologies, Technologies and Applications (SIMULTECH 2014))
We discuss a technique to analyze complex infinitely repeated games using techniques from the fields of game theory and simulations. Our research is motivated by the analysis of electronic markets with thousands of participants and possibly complex strategic behavior. We consider an example of a global market of composed IT services to demonstrate the use of our simulation technique. We present our current work in this area and we want to discuss further approaches for the future.

Multilevel Network Games - Abshoff, Sebastian; Cord-Landwehr, Andreas; Jung, Daniel; Skopalik, Alexander (Proceedings of the 10th International Conference on Web and Internet Economics (WINE))
We consider a multilevel network game, where nodes can improvetheir communication costs by connecting to a high-speed network.The n nodes are connected by a static network and each node can decideindividually to become a gateway to the high-speed network. The goalof a node v is to minimize its private costs, i.e., the sum (SUM-game) ormaximum (MAX-game) of communication distances from v to all othernodes plus a fixed price α > 0 if it decides to be a gateway. Between gatewaysthe communication distance is 0, and gateways also improve othernodes’ distances by behaving as shortcuts. For the SUM-game, we showthat for α ≤ n − 1, the price of anarchy is Θ (n/√α) and in this rangeequilibria always exist. In range α ∈ (n−1, n(n−1)) the price of anarchyis Θ(√α), and for α ≥ n(n − 1) it is constant. For the MAX-game, weshow that the price of anarchy is either Θ (1 + n/√α), for α ≥ 1, orelse 1. Given a graph with girth of at least 4α, equilibria always exist.Concerning the dynamics, both games are not potential games. For theSUM-game, we even show that it is not weakly acyclic.

HSkip+: A Self-Stabilizing Overlay Network for Nodes with Heterogeneous Bandwidths - Feldotto, Matthias; Scheideler, Christian; Graffi, Kalman (Proceedings of the 14th IEEE International Conference on Peer-to-Peer Computing (P2P))
In this paper we present and analyze HSkip+, a self-stabilizing overlay network for nodes with arbitrary heterogeneous bandwidths. HSkip+ has the same topology as the Skip+ graph proposed by Jacob et al. [PODC 2009] but its self-stabilization mechanism significantly outperforms the self-stabilization mechanism proposed for Skip+. Also, the nodes are now ordered according to their bandwidths and not according to their identifiers. Various other solutions have already been proposed for overlay networks with heterogeneous bandwidths, but they are not self-stabilizing. In addition to HSkip+ being self-stabilizing, its performance is on par with the best previous bounds on the time and work for joining or leaving a network of peers of logarithmic diameter and degree and arbitrary bandwidths. Also, the dilation and congestion for routing messages is on par with the best previous bounds for such networks, so that HSkip+ combines the advantages of both worlds. Our theoretical investigations are backed by simulations demonstrating that HSkip+ is indeed performing much better than Skip+ and working correctly under high churn rates.

Energy-efficient Scheduling Algorithms - Kling, Peter
In meiner Dissertation beschäftige ich mich mit dem Entwurf und der Analyse energieeffizienter Schedulingalgorithmen, insbesondere für sogenannte Speed-Scaling Modelle. Diese stellen das theoretische Pendant von Techniken wie AMDs PowerNOW! und Intels SpeedStep dar, welche es erlauben die Geschwindigkeit von Prozessoren zur Laufzeit an die derzeitigen Bedingungen anzupassen. Theoretische Untersuchungen solcher Modelle sind auf eine Arbeit von Yao, Demers und Shenker (FOCS'95) zurückzuführen. Hier kombinieren die Autoren klassisches Deadline-Scheduling mit einem Prozessor der Speed-Scaling beherrscht. Es gilt Jobs verschiedener Größe fristgerecht abzuarbeiten und die dabei verwendete Energie zu minimieren. Der Energieverbrauch des Prozessors wird durch eine konvexe Funktion $\POW\colon\R_{≥0}→\R_{≥0}$ modelliert, welche die Geschwindigkeit auf den Energieverbrauch abbildet.Meine Dissertation betrachtet verschiedene Varianten des ursprünglichen Speed-Scaling Modells. Forschungsrelevante Ergebnisse sind in den Kapiteln 3 bis 6 zu finden und erstrecken sich über die im Folgenden beschriebenen Aspekte:- Kapitel 3 und 4 betrachten verschiedene Price-Collecting Varianten des Originalproblems. Hier dürfen einzelne Deadlines verfehlt werden, sofern eine jobabhängige Strafe gezahlt wird. Ich entwerfe insbesondere Online-Algorithmen mit einer beweisbar guten Competitiveness. Dabei liefern meine Ergebnisse substantielle Verbesserungen bestehender Arbeiten und erweitern diese unter Anderem auf Szenarien mit mehreren Prozessoren.- In Kapitel 5 wird statt des klassischen Deadline-Schedulings eine Linearkombination der durchschnittlichen Antwortzeit und des Energieverbrauchs betrachtet. Die Frage, ob dieses Problem NP-schwer ist, stellt eine der zentralen Forschungsfragen in diesem Gebiet dar. Für eine relaxierte Form dieser Frage entwerfe ich einen effizienter Algorithmus und beweise seine Optimalität.- Das letzte Kapitel betrachtet ein Modell, welches – auf den ersten Blick – nicht direkt zur Speed-Scaling Literatur zählt. Hier geht es stattdessen um ein allgemeines Resource-Constrained Scheduling, in dem sich die Prozessoren zusammen eine gemeinsame, beliebig aufteilbare Ressource teilen. Ich untersuche die Komplexität des Problems und entwerfe verschiedene Approximationsalgorithmen.

Efficient Computation of Optimal Energy and Fractional Weighted Flow Trade-off Schedules - Antoniadis, Antonios; Barcelo, Neal; Consuegra, Mario; Kling, Peer; Nugent, Michael; Pruhs, Kirk; Scquizzato, Michele (Proceedings of the 31st Symposium on Theoretical Aspects of Computer Science (STACS))
We give a polynomial time algorithm to compute an optimal energy and fractional weighted flow trade-off schedule for a speed-scalable processor with discrete speeds.Our algorithm uses a geometric approach that is based on structural properties obtained from a primal-dual formulation of the problem.

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Automatic Reconstruction of Polygonal Room Models from 3D Point Clouds - Mertsching, Bärbel; Divband Soorati, Mohammad; Kotthauser, Tobias (IEEE International Conference on Robotics and Biomimetics (ROBIO))

Time delay implies cost on task switching: A model to investigate the efficiency of task partitioning - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas (Bulletin of Mathematical Biology)

Algorithmic Requirements for Swarm Intelligence in Differently Coupled Collective Systems - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Zahadat, Payam (Chaos, Solitons & Fractals)

Virtual Spatiality in Agent Controllers: Encoding Compartmentalization - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Schwarzer, Christopher; Michiels, Nico K.; Esparcia-Alcazar, Anna Isabel (Applications of Evolutionary Computation - 16th European Conference (EvoApplications 2013))

A Reductionist Approach to Hypothesis-Catching for the Analysis of Self-Organizing Decision-Making Systems - Hamann, Heiko (7th IEEE Int. Conf. on Self-Adaptive and Self-Organizing Systems (SASO 2013))

Speciation Dynamics: Generating Selective Pressure Towards Diversity - Hamann, Heiko; Lio, Pietro; Miglino, Orazio; Nicosia, Giuseppe; Nolfi, Stefano; Pavone, Mario (12th European Conference on Artificial Life (ECAL 2013))

Towards Swarm Calculus: Urn Models of Collective Decisions and Universal Properties of Swarm Performance - Hamann, Heiko (Swarm Intelligence)

Darstellung heterogener 3-D-Szenen in Echtzeit - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)
Viele virtuelle 3-D-Szenen im industriellen Bereich sind nicht gleichmäßig strukturiert, z.B. weil sie eine stark unterschiedliche Dichteverteilung der Polygone aufweisen. Für solch heterogene Daten existiert kein Algorithmus, der die Gesamtheit der Daten sowohl schnell als auch mit guter Qualität darstellen kann. Die Auswahl der richtigen Algorithmen für einzelne Szenenteile durch einen Experten ist zeitintensiv und in vielen Visualisierungssystemen nicht umzusetzen. Um dieses Problem zu lösen, setzt das hier vorgestellte Multi-Algorithmen-Rendering verschiedene Renderingalgorithmen gleichzeitig ein, um eine virtuelle 3-D-Szene darzustellen. Das Verfahren unterteilt die Szene dafür in einem Vorverarbeitungsschritt automatisch in geeignete Teilregionen und bestimmt deren Eigenschaften. Diese Daten werden zur Laufzeit dazu genutzt, um ständig für den aktuellen Standpunkt des Betrachters eine Abschätzung der Qualität und Laufzeit der zur Auswahl stehenden Renderingalgorithmen zu berechnen. Durch die Lösung eines Optimierungsproblems kann so bei vorgegebener Bildrate durch die passende Zuordnung der Algorithmen zu den Regionen die Bildqualität optimiert werden – bei automatischer Anpassung an die Leistungsfähigkeit der eingesetzten Hardware. In einer experimentellen Evaluierung vergleichen wir die Laufzeit und Bildqualität des Verfahrens mit denen verbreiteter Standardrenderingverfahren.

Spherical visibility sampling : preprocessed visibility for occlusion culling in complex 3D scenes - Eikel, Benjamin

Algorithmische Grundlagen für die Selbstorganisation von Roboterschwärmen - Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, R.; Nudelman, I.; Polevoy, Gleb (Networking, IEEE/ACM Transactions on)
In this paper, we define and study a new problem, referred to as the Dependent Unsplittable Flow Problem (D-UFP). We present and discuss this problem in the context of large-scale powerful (radar/camera) sensor networks, but we believe it has important applications on the admission of large flows in other networks as well. In order to optimize the selection of flows transmitted to the gateway, D-UFP takes into account possible dependencies between flows. We show that D-UFP is more difficult than NP-hard problems for which no good approximation is known. Then, we address two special cases of this problem: the case where all the sensors have a shared channel and the case where the sensors form a mesh and route to the gateway over a spanning tree.
Keywords: Approximation algorithms; Approximation methods; Bandwidth; Logic gates; Radar; Vectors; Wireless sensor networks; Dependent flow scheduling; sensor networks

Token Dissemination in Geometric Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Cord-Landwehr, Andreas; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013, Sophia Antipolis, France, September 5-6, 2013, Revised Selected Papers)
We consider the k-token dissemination problem, where k initially arbitrarily distributed tokens have to be disseminated to all nodes in a dynamic network (as introduced by Kuhn et al., STOC 2010). In contrast to general dynamic networks, our dynamic networks are unit disk graphs, i.e., nodes are embedded into the Euclidean plane and two nodes are connected if and only if their distance is at most R. Our worst-case adversary is allowed to move the nodes on the plane, but the maximum velocity v_max of each node is limited and the graph must be connected in each round. For this model, we provide almost tight lower and upper bounds for k-token dissemination if nodes are restricted to send only one token per round. It turns out that the maximum velocity v_max is a meaningful parameter to characterize dynamics in our model.

Profitable Scheduling on Multiple Speed-Scalable Processors - Kling, Peter; Pietrzyk, Peter (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We present a new online algorithm for profit-oriented scheduling on multiple speed-scalable processors.Moreover, we provide a tight analysis of the algorithm's competitiveness.Our results generalize and improve upon work by \citet{Chan:2010}, which considers a single speed-scalable processor.Using significantly different techniques, we can not only extend their model to multiprocessors but also prove an enhanced and tight competitive ratio for our algorithm.In our scheduling problem, jobs arrive over time and are preemptable.They have different workloads, values, and deadlines.The scheduler may decide not to finish a job but instead to suffer a loss equaling the job's value.However, to process a job's workload until its deadline the scheduler must invest a certain amount of energy.The cost of a schedule is the sum of lost values and invested energy.In order to finish a job the scheduler has to determine which processors to use and set their speeds accordingly.A processor's energy consumption is power $\Power{s}$ integrated over time, where $\Power{s}=s^{α}$ is the power consumption when running at speed $s$.Since we consider the online variant of the problem, the scheduler has no knowledge about future jobs.This problem was introduced by~\citet{Chan:2010} for the case of a single processor.They presented an online algorithm which is $α^{α}+2eα$-competitive.We provide an online algorithm for the case of multiple processors with an improved competitive ratio of $α^{α}$.

On Two-Party Communication Through Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 17th International Conference on Principles of Distributed Systems (OPODIS))
We study two-party communication in the context of directed dynamic networks that are controlled by an adaptive adversary. This adversary is able to change all edges as long as the networks stay strongly-connected in each round. In this work, we establish a relation between counting the total number of nodes in the network and the problem of exchanging tokens between two communication partners which communicate through a dynamic network. We show that the communication problem for a constant fraction of n tokens in a dynamic network with n nodes is at most as hard as counting the number of nodes in a dynamic network with at most 4n+3 nodes. For the proof, we construct a family of directed dynamic networks and apply a lower bound from two-party communication complexity.

Local and Online Algorithms for Facility Location - Pietrzyk, Peter
Diese Arbeit beschäftigt sich mit dem Facility Location Problem. Dies ist ein Optimierungsproblem, bei dem festgelegt werden muss an welchen Positionen Ressourcen zur Verfügung gestellt werden, so dass diese von Nutzern gut erreicht werden können. Es sollen dabei Kosten minimiert werden, die zum einen durch Bereitstellung von Ressourcen und zum anderen durch Verbindungskosten zwischen Nutzern und Ressourcen entstehen. Die Schwierigkeit des Problems liegt darin, dass man einerseits möglichst wenige Ressourcen zur Verfügung stellen möchte, andererseits dafür sorgen muss, dass sich Nutzer nicht all zu weit weg von Ressourcen befinden. Dies würde nämlich hohe Verbindungskosten nach sich ziehen. Das Facility Location Problem wurde bereits sehr intensiv in vielen unterschiedlichen Varianten untersucht. In dieser Arbeit werden drei Varianten des Problems modelliert und neue Algorithmen für sie entwickelt und bezüglich ihres Approximationsfaktors und ihrer Laufzeit analysiert. Jede dieser drei untersuchten Varianten hat einen besonderen Schwerpunkt. Bei der ersten Varianten handelt es sich um ein Online Problem, da hier die Eingabe nicht von Anfang an bekannt ist, sondern Schritt für Schritt enthüllt wird. Die Schwierigkeit hierbei besteht darin unwiderrufliche Entscheidungen treffen zu müssen ohne dabei die Zukunft zu kennen und trotzdem eine zu jeder Zeit gute Lösung angeben zu können. Der Schwerpunkt der zweiten Variante liegt auf Lokalität, die z.B. in Sensornetzwerken von großer Bedeutung ist. Hier soll eine Lösung verteilt und nur mit Hilfe von lokalen Information berechnet werden. Schließlich beschäftigt sich die dritte Variante mit einer verteilten Berechnung, bei welcher nur eine stark beschränkte Datenmenge verschickt werden darf und dabei trotzdem ein sehr guter Approximationsfaktor erreicht werden muss. Die bei der Analyse der Approximationsfaktoren bzw. der Kompetitivität verwendeten Techniken basieren zum großen Teil auf Abschätzung der primalen Lösung mit Hilfe einer Lösung des zugehörigen dualen Problems. Für die Modellierung von Lokalität wird das weitverbreitete LOCAL Modell verwendet. In diesem Modell werden für die Algorithmen subpolynomielle obere Laufzeitschranken gezeigt.

Hierarchies in Local Distributed Decision - Meyer auf der Heide, Friedhelm; Swirkot, Kamil
We study the complexity theory for the local distributed setting introduced by Korman, Peleg and Fraigniaud. They have defined three complexity classes LD (Local Decision), NLD (Nondeterministic Local Decision) and NLD^#n. The class LD consists of all languages which can be decided with a constant number of communication rounds. The class NLD consists of all languages which can be verified by a nondeterministic algorithm with a constant number of communication rounds. In order to define the nondeterministic classes, they have transferred the notation of nondeterminism into the distributed setting by the use of certificates and verifiers. The class NLD^#n consists of all languages which can be verified by a nondeterministic algorithm where each node has access to an oracle for the number of nodes. They have shown the hierarchy LD subset NLD subset NLD^#n. Our main contributions are strict hierarchies within the classes defined by Korman, Peleg and Fraigniaud. We define additional complexity classes: the class LD(t) consists of all languages which can be decided with at most t communication rounds. The class NLD-O(f) consists of all languages which can be verified by a local verifier such that the size of the certificates that are needed to verify the language are bounded by a function from O(f). Our main results are refined strict hierarchies within these nondeterministic classes.

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics

A Local Heuristic for Latency-Optimized Distributed Cloud Deployment - Keller, Matthias; Pawlik, Stefan; Pietrzyk, Peter; Karl, Holger (Proceedings of the 6th International Conference on Utility and Cloud Computing (UCC) workshop on Distributed cloud computing)
In Distributed Cloud Computing, applications are deployed across many data centres at topologically diverse locations to improved network-related quality of service (QoS). As we focus on interactive applications, we minimize the latency between users and an application by allocating Cloud resources nearby the customers. Allocating resources at all locations will result in the best latency but also in the highest expenses. So we need to find an optimal subset of locations which reduces the latency but also the expenses – the facility location problem (FLP). In addition, we consider resource capacity restrictions, as a resource can only serve a limited amount of users. An FLP can be globally solved. Additionally, we propose a local, distributed heuristic. This heuristic is running within the network and does not depend on a global component. No distributed, local approximations for the capacitated FLP have been proposed so far due to the complexity of the problem. We compared the heuristic with an optimal solution obtained from a mixed integer program for different network topologies. We investigated the influence of different parameters like overall resource utilization or different latency weights.

A Distributed Approximation Algorithm for Strongly Connected Dominating-Absorbent Sets in Asymmetric Wireless Ad-Hoc Networks - Markarian, Christine; Meyer auf der Heide, Friedhelm; Schubert, Michael (Proceedings of the 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics (ALGOSENSORS))
Dominating set based virtual backbones are used for rou-ting in wireless ad-hoc networks. Such backbones receive and transmit messages from/to every node in the network. Existing distributed algorithms only consider undirected graphs, which model symmetric networks with uniform transmission ranges. We are particularly interested in the well-established disk graphs, which model asymmetric networks with non-uniform transmission ranges. The corresponding graph theoretic problem seeks a strongly connected dominating-absorbent set of minimum cardinality in a digraph. A subset of nodes in a digraph is a strongly connected dominating-absorbent set if the subgraph induced by these nodes is strongly connected and each node in the graph is either in the set or has both an in-neighbor and an out-neighbor in it. We introduce the first distributed algorithm for this problem in disk graphs. The algorithm gives an O(k^4) -approximation ratio and has a runtime bound of O(Diam) where Diam is the diameter of the graph and k denotes the transmission ratio r_{max}/r_{min} with r_{max} and r_{min} being the maximum and minimum transmission range, respectively. Moreover, we apply our algorithm on the subgraph of disk graphs consisting of only bidirectional edges. Our algorithm gives an O(ln k) -approximation and a runtime bound of O(k^8 log^∗ n) , which, for bounded k , is an optimal approximation for the problem, following Lenzen and Wattenhofer’s Ω(log^∗ n) runtime lower bound for distributed constant approximation in disk graphs.

Spherical Visibility Sampling - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Computer Graphics Forum)
Many 3D scenes (e.g. generated from CAD data) are composed of a multitude of objects that are nested in each other. A showroom, for instance, may contain multiple cars and every car has a gearbox with many gearwheels located inside. Because the objects occlude each other, only few are visible from outside. We present a new technique, Spherical Visibility Sampling (SVS), for real-time 3D rendering of such -- possibly highly complex -- scenes. SVS exploits the occlusion and annotates hierarchically structured objects with directional visibility information in a preprocessing step. For different directions, the directional visibility encodes which objects of a scene's region are visible from the outside of the regions' enclosing bounding sphere. Since there is no need to store a separate view space subdivision as in most techniques based on preprocessed visibility, a small memory footprint is achieved. Using the directional visibility information for an interactive walkthrough, the potentially visible objects can be retrieved very efficiently without the need for further visibility tests. Our evaluation shows that using SVS allows to preprocess complex 3D scenes fast and to visualize them in real time (e.g. a Power Plant model and five animated Boeing 777 models with billions of triangles). Because SVS does not require hardware support for occlusion culling during rendering, it is even applicable for rendering large scenes on mobile devices.

Evaluation of Rendering Algorithms Using Position-Dependent Scene Properties - Jähn, Claudius; Eikel, Benjamin; Fischer, Matthias; Petring, Ralf; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
In order to evaluate the efficiency of algorithms for real-time 3D rendering, different properties like rendering time, occluded triangles, or image quality, need to be investigated. Since these properties depend on the position of the camera, usually some camera path is chosen, along which the measurements are performed. As those measurements cover only a small part of the scene, this approach hardly allows drawing conclusions regarding the algorithm's properties at arbitrary positions in the scene. The presented method allows the systematic and position-independent evaluation of rendering algorithms. It uses an adaptive sampling approach to approximate the distribution of a property (like rendering time) for all positions in the scene. This approximation can be visualized to produce an intuitive impression of the algorithm's behavior or be statistically analyzed for objectively rating and comparing algorithms. We demonstrate our method by evaluating performance aspects of a known occlusion culling algorithm.

Real-Time 3D Rendering of Heterogeneous Scenes - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
Many virtual 3D scenes, especially those that are large, are not structured evenly. For such heterogeneous data, there is no single algorithm that is able to render every scene type at each position fast and with the same high image quality. For a small set of scenes, this situation can be improved if different rendering algorithms are manually assigned to particular parts of the scene by an experienced user. We introduce the Multi-Algorithm-Rendering method. It automatically deploys different rendering algorithms simultaneously for a broad range of scene types. The method divides the scene into subregions and measures the behavior of different algorithms for each region in a preprocessing step. During runtime, this data is utilized to compute an estimate for the quality and running time of the available rendering algorithms from the observer's point of view. By solving an optimizing problem, the image quality can be optimized by an assignment of algorithms to regions while keeping the frame rate almost constant.

On-The-Fly Computing: A Novel Paradigm for Individualized IT Services - Happe, Markus; Kling, Peter; Plessl, Christian; Platzner, Marco; Meyer auf der Heide, Friedhelm (Proceedings of the 9th IEEE Workshop on Software Technology for Future embedded and Ubiquitous Systems (SEUS))
In this paper we introduce “On-The-Fly Computing”, our vision of future IT services that will be provided by assembling modular software components available on world-wide markets. After suitable components have been found, they are automatically integrated, configured and brought to execution in an On-The-Fly Compute Center. We envision that these future compute centers will continue to leverage three current trends in large scale computing which are an increasing amount of parallel processing, a trend to use heterogeneous computing resources, and—in the light of rising energy cost—energy-efficiency as a primary goal in the design and operation of computing systems. In this paper, we point out three research challenges and our current work in these areas.

Parallel Macro Pipelining on the Intel SCC Many-Core Computer - Suess, Tim; Schoenrock, Andrew; Meisner, Sebastian; Plessl, Christian (Proc. Int. Symp. on Parallel and Distributed Processing Workshops (IPDPSW))

Impact of Neuron Models and Network Structure on Evolving Modular Robot Neural Network Controllers - Hamann, Heiko; Stradner, Jürgen; Bredeche, Nicolas; Cazenille, Leo (14th Annual Genetic and Evolutionary Computation Conference, GECCO 2012)
This paper investigates the properties required to evolve Artificial Neural Networks for distributed control in modular robotics, which typically involves non-linear dynamics and complex interactions in the sensori-motor space. We investigate the relation between macro-scale properties (such as modularity and regularity) and micro-scale properties in Neural Network controllers. We show how neurons capable of multiplicative-like arithmetic operations may increase the performance of controllers in several ways whenever challenging control problems with non-linear dynamics are involved. This paper provides evidence that performance and robustness of evolved controllers can be improved by a combination of carefully chosen micro- and macro-scale neural network properties.

Towards Morphological Flexibility: Modular Robotics and Bio-inspired Control - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen (Austrian Robotics Workshop (Operational Programme Slovenia-Austria))
As a contribution to the efforts towards robotic systems of higher flexibility we present our concept of morphologically dynamic robots. Within the projects SYMBRION and REPLICATOR, that focus on modular robotics, we have developed bio-inspired control techniques to achieve new concepts of dynamic, autonomous morphological structures. We propose three modes of coupling between robot modules: swarm, team, and organism mode. We demonstrate our concepts along with simple robot experiments.

On-line, On-board Evolution of Reaction-Diffusion Control for Self-Adaptation - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Zahadat, Payam; Adami, Christoph; Bryson, David M.; Ofria, Charles; Pennock, Robert T. (Alife XIII)

Self-organized pattern formation in a swarm system as a transient phenomenon of non-linear dynamics - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Mathematical and Computer Modelling of Dynamical Systems)

A Hormone-Based Controller for Evaluation-Minimal Evolution in Decentrally Controlled Systems - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Artificial Life)
One of the main challenges in automatic controller synthesis is to develop methods that can successfully be applied for complex tasks. The difficulty is increased even more in the case of settings with multiple interacting agents. We apply the artificial homeostatic hormone system (AHHS) approach, which is inspired by the signaling network of unicellular organisms, to control a system of several independently acting agents decentrally. The approach is designed for evaluation-minimal, artificial evolution in order to be applicable to complex modular robotics scenarios. The performance of AHHS controllers is compared with neuroevolution of augmenting topologies (NEAT) in the coupled inverted pendulums benchmark. AHHS controllers are found to be better for multimodular settings. We analyze the evolved controllers with regard to the usage of sensory inputs and the emerging oscillations, and we give a nonlinear dynamics interpretation. The generalization of evolved controllers to initial conditions far from the original conditions is investigated and found to be good. Similarly, the performance of controllers scales well even with module numbers different from the original domain the controller was evolved for. Two reference implementations of a similar controller approach are reported and shown to have shortcomings. We discuss the related work and conclude by summarizing the main contributions of our work.

Analysis of emergent symmetry breaking in collective decision making - Hamann, Heiko; Schmickl, Thomas; Wörn, Heinz; Crailsheim, Karl (Neural Computing and Applications)

Towards Swarm Calculus: Universal Properties of Swarm Performance and Collective Decisions - Hamann, Heiko; Engelbrecht, Andreas; Birattari, Mauro; Dorigo, Marco; Blum, Christian; Stuetzle, Thomas; Christensen, Anders Lyhne; Gross, Roderich (Swarm Intelligence: 8th International Conference, ANTS 2012)

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, Reuven; Nudelman, Ilia; Polevoy, Gleb (Infocom'2012, Orlando, Florida)

Smoothed analysis of left-to-right maxima with applications - Damerow, Valentina; Manthey, Bodo; Meyer auf der Heide, Friedhelm; Räcke, Harald; Scheideler, Christian; Sohler, Christian; Tantau, Till (Transactions on Algorithms)
A left-to-right maximum in a sequence of n numbers s_1, …, s_n is a number that is strictly larger than all preceding numbers. In this article we present a smoothed analysis of the number of left-to-right maxima in the presence of additive random noise. We show that for every sequence of n numbers s_i ∈ [0,1] that are perturbed by uniform noise from the interval [-ε,ε], the expected number of left-to-right maxima is Θ(&sqrt;n/ε + log n) for ε>1/n. For Gaussian noise with standard deviation σ we obtain a bound of O((log3/2 n)/σ + log n).We apply our results to the analysis of the smoothed height of binary search trees and the smoothed number of comparisons in the quicksort algorithm and prove bounds of Θ(&sqrt;n/ε + log n) and Θ(n/ε+1&sqrt;n/ε + n log n), respectively, for uniform random noise from the interval [-ε,ε]. Our results can also be applied to bound the smoothed number of points on a convex hull of points in the two-dimensional plane and to smoothed motion complexity, a concept we describe in this article. We bound how often one needs to update a data structure storing the smallest axis-aligned box enclosing a set of points moving in d-dimensional space.

Slow Down & Sleep for Profit in Online Deadline Scheduling - Cord-Landwehr, Andreas; Kling, Peter; Mallmann Trenn, Fredrik (Proceedings of the 1st Mediterranean Conference on Algorithms (MedAlg))
We present and study a new model for energy-aware and profit-oriented scheduling on a single processor.The processor features dynamic speed scaling as well as suspension to a sleep mode.Jobs arrive over time, are preemptable, and have different sizes, values, and deadlines.On the arrival of a new job, the scheduler may either accept or reject the job.Accepted jobs need a certain energy investment to be finished in time, while rejected jobs cause costs equal to their values.Here, power consumption at speed $s$ is given by $P(s)=s^{α}+β$ and the energy investment is power integrated over time.Additionally, the scheduler may decide to suspend the processor to a sleep mode in which no energy is consumed, though awaking entails fixed transition costs $γ$.The objective is to minimize the total value of rejected jobs plus the total energy.Our model combines aspects from advanced energy conservation techniques (namely speed scaling and sleep states) and profit-oriented scheduling models.We show that rejection-oblivious schedulers (whose rejection decisions are not based on former decisions) have – in contrast to the model without sleep states – an unbounded competitive ratio.It turns out that the jobs' value densities (the ratio between a job's value and its work) are crucial for the performance of such schedulers.We give an algorithm whose competitiveness nearly matches the lower bound w.r.t\text{.} the maximum value density.If the maximum value density is not too large, the competitiveness becomes $α^{α}+2eα$.Also, we show that it suffices to restrict the value density of low-value jobs only.Using a technique from \cite{Chan:2010} we transfer our results to processors with a fixed maximum speed.

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

Local strategies for robot formation problems - Kempkes, Barbara
Wir betrachten eine Gruppe von mobilen, autonomen Robotern in einem ebenen Gelände. Es gibt keine zentrale Steuerung und die Roboter müssen sich selbst koordinieren. Zentrale Herausforderung dabei ist, dass jeder Roboter nur seine unmittelbare Nachbarschaft sieht und auch nur mit Robotern in seiner unmittelbaren Nachbarschaft kommunizieren kann. Daraus ergeben sich viele algorithmische Fragestellungen. In dieser Arbeit wird untersucht, unter welchen Voraussetzungen die Roboter sich auf einem Punkt versammeln bzw. eine Linie zwischen zwei festen Stationen bilden können. Dafür werden mehrere Roboter-Strategien in verschiedenen Bewegungsmodellen vorgestellt. Diese Strategien werden auf ihre Effizienz hin untersucht. Es werden obere und untere Schranken für die benötigte Anzahl Runden und die Bewegungsdistanz gezeigt. In einigen Fällen wird außerdem die benötigte Bewegungsdistanz mit derjenigen Bewegungsdistanz verglichen, die eine optimale globale Strategie auf der gleichen Instanz benötigen würde. So werden kompetititve Faktoren hergeleitet.

Distributed Computing in Fault-Prone Dynamic Networks - Brandes, Philipp; Meyer auf der Heide, Friedhelm (Proceedings of the 4th Workshop on Theoretical Aspects of Dynamic Distributed Systems (TADDS))
Dynamics in networks is caused by a variety of reasons, like nodes moving in 2D (or 3D) in multihop cellphone networks, joins and leaves in peer-to-peer networks, evolution in social networks, and many others. In order to understand such kinds of dynamics, and to design distributed algorithms that behave well under dynamics, many ways to model dynamics are introduced and analyzed w.r.t. correctness and eciency of distributed algorithms. In [16], Kuhn, Lynch, and Oshman have introduced a very general, worst case type model of dynamics: The edge set of the network may change arbitrarily from step to step, the only restriction is that it is connected at all times and the set of nodes does not change. An extended model demands that a xed connected subnetwork is maintained over each time interval of length T (T-interval dynamics). They have presented, among others, algorithms for counting the number of nodes under such general models of dynamics.In this paper, we generalize their models and algorithms by adding random edge faults, i.e., we consider fault-prone dynamic networks: We assume that an edge currently existing may fail to transmit data with some probability p. We rst observe that strong counting, i.e., each node knows the correct count and stops, is not possible in a model with random edge faults. Our main two positive results are feasibility and runtime bounds for weak counting, i.e., stopping is no longer required (but still a correct count in each node), and for strong counting with an upper bound, i.e., an upper bound N on n is known to all nodes.

Basic Network Creation Games with Communication Interests - Cord-Landwehr, Andreas; Huellmann (married name: Eikel), Martina; Kling, Peter; Setzer, Alexander (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
Network creation games model the creation and usage costs of networks formed by a set of selfish peers.Each peer has the ability to change the network in a limited way, e.g., by creating or deleting incident links.In doing so, a peer can reduce its individual communication cost.Typically, these costs are modeled by the maximum or average distance in the network.We introduce a generalized version of the basic network creation game (BNCG).In the BNCG (by Alon et al., SPAA 2010), each peer may replace one of its incident links by a link to an arbitrary peer.This is done in a selfish way in order to minimize either the maximum or average distance to all other peers.That is, each peer works towards a network structure that allows himself to communicate efficiently with all other peers.However, participants of large networks are seldom interested in all peers.Rather, they want to communicate efficiently with a small subset only.Our model incorporates these (communication) interests explicitly.Given peers with interests and a communication network forming a tree, we prove several results on the structure and quality of equilibria in our model.We focus on the MAX-version, i.e., each node tries to minimize the maximum distance to nodes it is interested in, and give an upper bound of O(\sqrt(n)) for the private costs in an equilibrium of n peers.Moreover, we give an equilibrium for a circular interest graph where a node has private cost Omega(\sqrt(n)), showing that our bound is tight.This example can be extended such that we get a tight bound of Theta(\sqrt(n)) for the price of anarchy.For the case of general networks we show the price of anarchy to be Theta(n).Additionally, we prove an interesting connection between a maximum independent set in the interest graph and the private costs of the peers.

An Algorithm for Facility Leasing - Meyer auf der Heide, Friedhelm; Pietrzyk, Peter; Kling, Peter (Proceedings of the 19th International Colloquium on Structural Information & Communication Complexity (SIROCCO))
We consider an online facility location problem where clients arrive over time and their demands have to be served by opening facilities and assigning the clients to opened facilities. When opening a facility we must choose one of K different lease types to use. A lease type k has a certain lease length lk. Opening a facility i using lease type k causes a cost of f k i and ensures that i is open for the next lk time steps. In addition to costs for opening facilities, we have to take connection costs ci j into account when assigning a client j to facility i. We develop and analyze the first online algorithm for this problem that has a time-independent competitive factor.This variant of the online facility location problem was introduced by Nagarajan and Williamson [7] and is strongly related to both the online facility problem by Meyerson [5] and the parking permit problem by Meyerson [6]. Nagarajan and Williamson gave a 3-approximation algorithm for the offline problem and an O(Klogn)-competitive algorithm for the online variant. Here, n denotes the total number of clients arriving over time. We extend their result by removing the dependency on n (and thereby on the time). In general, our algorithm is O(lmax log(lmax))-competitive. Here lmax denotes the maximum lease length. Moreover, we prove that it is O(log2(lmax))-competitive for many “natural” cases. Such cases include, for example, situations where the number of clients arriving in each time step does not vary too much, or is non-increasing, or is polynomially bounded in lmax.

Adaptive Verbindungsstrategien in dynamischen Suchnetzwerken - Eidens, Fabian

Continuous Local Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Experimental Algorithms)

Optimal and competitive runtime bounds for continuous, local gathering of mobile robots - Kempkes, Barbara; Kling, Peter; Meyer auf der Heide, Friedhelm (Proceedinbgs of the 24th ACM symposium on Parallelism in algorithms and architectures - SPAA '12)

Local, Self-organizing Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems)

Asynchronous Occlusion Culling on Heterogeneous PC Clusters for Distributed 3D Scenes - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
We present a parallel rendering system for heterogeneous PC clusters to visualize massive models. One single, powerful visualization node is supported by a group of backend nodes with weak graphics performance. While the visualization node renders the visible objects, the backend nodes asynchronously perform visibility tests and supply the front end with visible scene objects. The visualization node stores only currently visible objects in its memory, while the scene is distributed among the backend nodes’ memory without redundancy. To efficiently compute the occlusion tests in spite of that each backend node stores only a fraction of the original geometry, we complete the scene by adding highly simplified versions of the objects stored on other nodes. We test our system with 15 backend nodes. It is able to render a ≈ 350,M polygons (≈ 8.5,GiB) large aircraft model with 20, to 30,fps and thus allows a walk-through in real-time.

Dynamic Load Balancing in Peer-to-Peer Networks - Korzeniowski, Miroslaw

Stackelberg Network Pricing Games - Briest, Patrick; Krysta, Piotr; Hoefer, Martin (Algorithmica)

PADrend: Platform for Algorithm Development and Rendering - Jähn, Claudius; Petring, Ralf; Eikel, Benjamin (Augmented & Virtual Reality in der Produktentstehung)
In dieser Arbeit stellen wir ein flexibles System zur Entwicklung und Evaluation von 3-D-Renderingalgorithmen vor, das die Visualisierung komplexer virtueller Szenen auf einem breiten Spektrum an Geräten erlaubt. Die Aufbereitung und Echtzeitdarstellung solcher virtueller Szenen, wie sie beispielsweise aus detaillierten CAD-Daten erzeugt werden, stellt in vielerlei Hinsicht eine algorithmische und technische Herausforderung dar. Die 3-D-Szenendaten können nach dem Dateiimport aus einem Austauschformat in eine Vielzahl unterschiedlicher Datenstrukturen überführt werden. Es muss ein geeignetes Renderingverfahren ausgewählt und eingestellt werden, welches sowohl die Eigenschaften der Szene (Zahl der Polygone, Grad der Verdeckung etc.) als auch die Fähigkeiten der Hardware berücksichtigt. Auf der einen Seite stellt die Darstellung auf mobilen Endgeräten wie Smartphones besonders hohe Anforderungen aufgrund der Speicherbeschränkung und der geringen Leistungsfähigkeit der Grafikhardware. Auf der anderen Seite stehen bei Großprojektionssystemen, wie beispielsweise dem HD-Visualisierungscenter des Heinz Nixdorf Instituts, die hohe Bildqualität bei stereoskopischer Darstellung und die Unterstützung von Trackingsystemen im Vordergrund. Der Fokus des von uns entwickelten Systems PADrend liegt in der Bereitstellung einer flexiblen und leicht erweiterbaren Grundlage für die Entwicklung und Evaluation von 3-D-Renderingalgorithmen und räumlichen Datenstrukturen im Bereich der Forschung und der universitären Ausbildung. Durch den modularen Aufbau und die große Bandbreite an unterstützten Systemen wird gewährleistet, dass eine Vielzahl unterschiedlicher Entwicklungen und Anwendungen auf PADrend aufsetzen können. In diesem Artikel geben wir einen Überblick über den Aufbau und die Fähigkeiten des Systems. Des Weiteren geben wir ein Beispiel für ein Anwendungsszenario, in dem PADrend eingesetzt wird: die Visualisierung von architektonischen Modellen auf einem Multiprojektionssystem.

Coupled inverted pendulums: A benchmark for evolving decentral controllers in modular robotics - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl; Krasnogor, Natalio; Luca Lanzi, Pier (Proceedings of the 13th Annual Genetic and Evolutionary Computation Conference, GECCO 2011)
The challenging scientific field of self-reconfiguring modular robotics (i.e., decentrally controlled 'super-robots' based on autonomous, interacting robot modules with variable morphologies) calls for novel paradigms of designing robot controllers. One option is the approach of evolutionary robotics. In this approach, the challenge is to achieve high evaluation numbers with the available resources which may even affect the feasibility of this approach. Simulations are usually applied at least in a preliminary stage of research to support controller design. However, even simulations are computationally expensive which gets even more burdensome once comprehensive studies and comparisons between different controller designs and approaches have to be done. Hence, a benchmark with low computational cost is needed that still contains the typical challenges of decentral control, is comparable, and easily manageable. We propose such a benchmark and report an empirical study of its characteristics including the transition from the single-robot setting to the multi-robot setting, typical local optima, and properties of adaptive walks through the fitness landscape.

Thermodynamics of Emergence: Langton's Ant Meets Boltzmann - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (IEEE Symposium on Artificial Life (IEEE ALIFE 2011))
The current definitions of emergence have no effects in the context of artificial life that could convincingly be called `constructive'. They are rather descriptive labels or tests. In order to get towards recipes of generating emergence we need to know systemic characteristics that help during the design phase of artificial life systems and worlds. In this paper, we develop and discuss five hypotheses that are not meant to be irrevocable but rather thought-provoking. We introduce two modeling approaches for Langton's ant to clarify these hypotheses. Then we discuss general properties of systems, such as (ir-)reversibility, dependence on initial states, computation, discreetness, and undecidable properties of system states.

Evolving for Creativity: Maximizing Complexity in a Self-organized Multi-particle System - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (10th European Conference on Artificial Life (ECAL'09))

Robotic Organisms: Artificial Homeostatic Hormone System and Virtual Embryogenesis as Examples for Adaptive Reaction-Diffusion Controllers - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Rona; Fitch, Robert (Robotic Organisms: Artificial Homeostatic Hormone System and Virtual Embryogenesis as Examples)

BEECLUST: A Swarm Algorithm Derived from Honeybees - Hamann, Heiko; Schmickl, Thomas (Bio-inspired Computing and Communication Networks)

Evolving a novel bio-inspired controller in reconfigurable robots - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Kampis, Gyoergy; Szathmary, Eoers (Advances in Artificial Life, 10th European Conference, ECAL 2009)

Embodiment of Honeybee's Thermotaxis in a Mobile Robot Swarm - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl; Thenius, Ronald; Kengyel, Daniela (10th European Conference on Artificial Life (ECAL'09))

Explaining Emergent Behavior in a Swarm System Based on an Inversion of the Fluctuation Theorem - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Advances in Artificial Life, ECAL 2011: Proceedings of the 11th European Conference on the Synthesis and Simulation of Living Systems)

Major Feedback Loops Supporting Artificial Evolution in Multi-modular Robotics - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Winkler, Lutz (New Horizons in Evolutionary Robotics)

Modelling a hormone-inspired controller for individual- and multi-modular robotic systems - Schmickl, Thomas; Hamann, Heiko; Crailsheim, Karl (Mathematical and Computer Modelling of Dynamical Systems)

Approximative occlusion culling using the hull tree - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias (Proceedings of the Graphics Interface 2011 Conference, May 25-27, St. John's, Newfoundland, Canada)
Occlusion culling is a common approach to accelerate real-time rendering of polygonal 3D-scenes by reducing the rendering load. Especially for large scenes, it is necessary to remove occluded objects to achieve a frame rate that provides an interactive environment. In order to benefit from the culling properly, often hierarchical data structures are used. These data structures typically create a spatial subdivision of a given scene into axis-aligned bounding boxes. These boxes can be tested quickly, but they are not very precise. By using these boxes, the included objects are detected as visible, even if other objects occlude them (false-positives). To get perfect results, the models original geometry included in the box has to be tested, but this would require too much computational power. To overcome this problem, original objects approximations could be used, but typical methods for mesh simplification cannot be applied, because they do not create an outer hull for a given object. We present a model simplification algorithm, which generates simple outer hulls, consisting of only few more triangles than a box, while preserving an objects shape better than a corresponding bounding box. This approach is then extended to a hierarchical data structure, the so-called hull tree, that can be generated for a given scene to improve the visibility tests. Next, we present an approximative rendering algorithm, which combines the features of the hull tree with the use of inner hulls for efficient occlusion detection and global state-sorting of the visible objects.

Simulation aided, knowledge based routing for AGVs in a distribution warehouse - Klaas, Alexander; Laroque, Christoph; Dangelmaier, Wilhelm; Fischer, Matthias (Proceedings of the 2011 Winter Simulation Conference (WSC))

Ein paralleles Out-of-Core Renderingsystem für Standard-Rechnernetze - Suess, Tim; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm; Koch, Clemens (Augmented & Virtual Reality in der Produktentstehung)

Parallel Real-Time Rendering using Heterogeneous PC Clusters - Suess, Tim

Algorithms for Dynamic Geometric Data Streams - Frahling, Gereon

Power-Aware Online File Allocation in Dynamic Networks - Mehler, Jan

Peer-to-Peer Based Parallel Web Computing - Gehweiler, Joachim
Web computing is a variant of parallel computing where the idle times of PCs donated by worldwide distributed users are employed to execute parallel programs. In this thesis we consider a web computing variant with two important properties: First, we support the execution of coupled, massively parallel algorithms (rather than distributed data processing). And second, we organize the system in peer-to-peer fashion. We present the Paderborn University BSP-based Web Computing (PUB-Web) library, which supports the execution of parallel programs in the bulk-synchronous style (BSP) in such a web computing setting. In this thesis, we focus on important technical and algorithmic aspects, in particular: In order to schedule processes with respect to the currently available computing power, which continually changes in an unpredictable fashion, we need intelligent load balancing algorithms and -- as a basic precondition -- the technical ability to migrate threads at runtime. To achieve the latter in a way suitable for production use, compatible with recent Java versions, available for all important platforms, and easy-to-use for developers, we develop the PadMig thread migration and checkpointing library. In order to tackle the distributed load balancing problem, we present an algorithm based on Distributed Heterogeneous Hash-Tables. In order to judge the quality of the schedules produced, we perform extensive experiments to compare several variants of the DHHT-based load balancer with the well- established Work Stealing algorithm, using realistic input data obtained by profiling the utilization of several hundred PCs for a period of several months. Beside the available computing power, we finally also consider the network bandwidth as a secondary criterion for load balancing. For this purpose, we cluster the PUB-Web network according to bandwidth, employing a novel, fault-tolerant, adaptive, and scaling distributed clustering algorithm called DiDiC. In order to judge the quality of the clusterings produces by DiDiC, we experimentally compare it to the well-established MCL algorithm using a simulator.

The car sharing problem - Briest, Patrick; Raupach, Christoph (Proceedings of the 23rd ACM symposium on Parallelism in algorithms and architectures - SPAA '11)

Verfahren zur redundanten Datenplatzierung in skalierbaren Speichersystemen - Effert, Sascha

Approximation Techniques for Utilitarian Mechanism Design - Briest, Patrick; Krysta, Piotr; Vöcking, Berthold (SIAM Journal on Computing)
This paper deals with the design of efficiently computable incentive-compatible mechanisms for combinatorial optimization problems with single-minded agents each possibly having multiple private parameters. We focus on approximation algorithms for NP-hard mechanism design problems. These algorithms need to satisfy certain monotonicity properties to ensure truthfulness. Since most of the known approximation techniques do not fulfill these properties, we study alternative techniques. Our first contribution is a quite general method to transform a pseudopolynomial algorithm into a monotone fully polynomial time approximation scheme (FPTAS). This can be applied to various problems like, e.g., knapsack, constrained shortest path, or job scheduling with deadlines. For example, the monotone FPTAS for the knapsack problem gives a very efficient, truthful mechanism for single-minded multiunit auctions. The best previous result for such auctions was a 2-appro-xi-ma-tion. In addition, we present a monotone PTAS for the generalized assignment problem with any constant number of private parameters per agent. The most efficient way to solve packing integer programs (PIPs) is linear programming–based randomized rounding, which also is in general not monotone. We show that primal-dual greedy algorithms achieve almost the same approximation ratios for PIPs as randomized rounding. The advantage is that these algorithms are inherently monotone. This way, we can significantly improve the approximation ratios of truthful mechanisms for various fundamental mechanism design problems like single-minded combinatorial auctions (CAs), unsplittable flow routing, and multicast routing. Our primal-dual approximation algorithms can also be used for the winner determination in CAs with general bidders specifying their bids through an oracle.

Buying Cheap Is Expensive: Approximability of Combinatorial Pricing Problems - Briest, Patrick; Krysta, Piotr (SIAM Journal on Computing)
We investigate nonparametric multiproduct pricing problems, in which we want to find revenue maximizing prices for products $\mathcal{P}$ based on a set of customer samples $\mathcal{C}$. We mostly focus on the unit-demand case, in which products constitute strict substitutes and each customer aims to purchase a single product. In this setting a customer sample consists of a number of nonzero values for different products and possibly an additional product ranking. Once prices are fixed, each customer chooses to buy one of the products she can afford based on some predefined selection rule. We distinguish between the min-buying, max-buying, and rank-buying models. Some of our results also extend to single-minded pricing, in which case products are strict complements and every customer seeks to buy a single set of products, which she purchases if the sum of prices is below her valuation for that set. For the min-buying model we show that the revenue maximization problem is not approximable within factor $\mathcal{O}(\log^{ε}|\mathcal{C}|)$ for some constant $ε>0$, unless $NP\subseteqDTIME(n^{\mathcal{O}(\log\log n)})$, thereby almost closing the gap between the known algorithmic results and previous lower bounds. We also prove inapproximability within $\mathcal{O}(\ell^{ε})$, $\ell$ being an upper bound on the number of nonzero values per customer, and $\mathcal{O}(|\mathcal{P}|^{ε})$ under slightly stronger assumptions and provide matching upper bounds. Surprisingly, these hardness results hold even if a price ladder constraint, i.e., a predefined order on the prices of all products, is given. Without the price ladder constraint we obtain similar hardness results for the special case of uniform valuations, i.e., the case that every customer has identical values for all the products she is interested in, assuming specific hardness of the balanced bipartite independent set problem in constant degree graphs or hardness of refuting random 3CNF formulas. Introducing a slightly more general problem definition in which customers are given as an explicit probability distribution, we obtain inapproximability within $\mathcal{O}(|\mathcal{P}|^{ε})$ assuming $NP\nsubseteq\bigcap_{δ>0}BPTIME(2^{\mathcal{O}(n^{δ})})$. These results apply to single-minded pricing as well. For the max-buying model a polynomial-time approximation scheme exists if a price ladder is given. We give a matching lower bound by proving strong NP-hardness. Assuming limited product supply, we analyze a generic local search algorithm and prove that it is 2-approximate. Finally, we discuss implications for the rank-buying model.

Collisionless Gathering of Robots with an Extent - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; auf der Heide, Friedhelm Meyer; Raupach, Christoph; Swierkot, Kamil; et al. (SOFSEM 2011: Theory and Practice of Computer Science)

A New Approach for Analyzing Convergence Algorithms for Mobile Robots - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (Automata, Languages and Programming)

An Easy Extendable Modeling Framework for Discrete Event Simulation Models and their Visualization - Renken, Hendrik; Laroque, Christoph; Fischer, Matthias (Proceedings of The 25th European Simulation and Modelling Conference - ESM2011)

Parallel Out-of-Core Occlusion Culling - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm
We present a parallel rendering system for PC-Clusters to visualize large 3D scenes. One single visualization node, equipped with a high-end graphics adapter, is supported by a group of backend nodes with weak graphics performance. The objects of the scene are distributed among these backend nodes, they serve two purposes: First, they provide an out-of-core memory system for the visualization node. Second, they assist the visualization node's rendering by performing visibility calculations and only sending visible objects to the visualization node. In order to obtain fast rendering with our system, we have to distribute the objects among the backend nodes in a way that does not only guarantee an even distribution of the objects, but also an even distribution of the visibility calculations and the amount of data send to the visualization node. We identify necessary properties of the distribution and argue that a random distribution is a good candidate. Further, in order to reduce the number of objects sent to the visualization node per frame, we employ an approximate hierarchical occlusion culling in each backend node. For this, they are equipped, in addition to the objects assigned to them, with simplified versions of the other objects of the 3D scene. The visualization node is equipped with 512 MiB video memory and supported by 15 backend nodes. This system is able to render a approx. 350 million polygons (approx. 8.5 GiB) large aircraft model between 20 - 30 fps and thus allows a walkthrough in real-time.

Considerate Equilibrium - Vöcking, Berthold; Hoefer, Martin; Skopalik, Alexander; Penn, Michal; Polukarov, Maria (IJCAI 2011, Proceedings of the 22nd International Joint Conference on Artificial Intelligence,)

Local Approximation Algorithms for the Uncapacitated Metric Facility Location Problem in Power-Aware Sensor Networks - Abshoff, Sebastan; Cord-Landwehr, Andreas; Degener, Bastian; Kempkes, Barbara; Pietrzyk, Peter (Proceedings of the 7th International Symposium on Algorithms for Sensor Systems, Wireless Ad Hoc Networks and Autonomous Mobile Entities (ALGOSENSORS))
We present two distributed, constant factor approximation algorithms for the metric facility location problem. Both algorithms have been designed with a strong emphasis on applicability in the area of wireless sensor networks: in order to execute them, each sensor node only requires limited local knowledge and simple computations. Also, the algorithms can cope with measurement errors and take into account that communication costs between sensor nodes do not necessarily increase linearly with the distance, but can be represented by a polynomial. Since it cannot always be expected that sensor nodes execute algorithms in a synchronized way, our algorithms are executed in an asynchronous model (but they are still able to break symmetry that might occur when two neighboring nodes act at exactly the same time). Furthermore, they can deal with dynamic scenarios: if a node moves, the solution is updated and the update affects only nodes in the local neighborhood. Finally, the algorithms are robust in the sense that incorrect behavior of some nodes during some round will, in the end, still result in a good approximation. The first algorithm runs in expected O(log_{1+ε} n) communication rounds and yields a \my^4(1+4\my^2(1+ε)^{1/p})^p approximation, while the second has a running time of expected O(log^2_{1+ε} n) communication rounds and an approximation factor of \my^4(1 + 2(1 + ε)^{1/p})^p. Here, ε > 0 is an arbitrarily small constant, p the exponent of the polynomial representing the communication costs, and \my the relative measurement error.

Complexity Classes for Local Computation - Swierkot, Kamil

An Experimental Comparison of Load Balancing Strategies in a Web Computing Environment - Gehweiler, Joachim; Kling, Peter; Meyer auf der Heide, Friedhelm (Proceedings of the 9th International Conference on Parallel Processing and Applied Mathematics (PPAM))
Web Computing is a variant of parallel computing where the idle times of PCs donated by worldwide distributed users are employed to execute parallel programs. The PUB-Web library developed by us supports this kind of usage of computing resources. A major problem for the efficient execution of such parallel programs is load balancing. In the Web Computing context, this problem becomes more difficult because of the dynamic behavior of the underlying "parallel computer": the set of available processors (donated PCs) as well as their availability (idle times) change over time in an unpredictable fashion.In this paper, we experimentally evaluate and compare load balancing algorithms in this scenario, namely a variant of the well-established Work Stealing algorithm and strategies based on a heterogeneous version of distributed hash-tables (DHHTs) introduced recently. In order to run a meaningful experimental evaluation, we employ, in addition to our Web Computing library PUB-Web, realistic data sets for the job input streams and for the dynamics of the availability of the resources.Our experimental evaluations suggest that Work Stealing is the better strategy if the number of processes ready to run matches the number of available processors. But a suitable variant of DHHTs outperforms Work Stealing if there are significantly more processes ready to run than available processors.

23rd Annual ACM Symposium on Parallelism in Algorithms and Architectures

Collisionless Gathering of Robots with an Extent - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (37th International Conference on Current Trends in Theory and Practice of Computer Science (SOFSEM 2011))
Gathering n mobile robots in one single point in the Euclidean plane is a widely studied problem from the area of robot formation problems. Classically, the robots are assumed to have no physical extent, and they are able to share a position with other robots. We drop these assumptions and investigate a similar problem for robots with (a spherical) extent: the goal is to gather the robots as close together as possible. More exactly, we want the robots to form a sphere with minimum radius around a predefined point. We propose an algorithm for this problem which synchronously moves the robots towards the center of the sphere unless they block each other. In this case, if possible, the robots spin around the center of the sphere. We analyze this algorithm experimentally in the plane. If R is the distance of the farthest robot to the center of the sphere, the simulations indicate a runtime which is linear in n and R. Additionally, we prove a theoretic upper bound for the runtime of O(nR) for a discrete version of the problem. Simulations also suggest a runtime of O(n + R) for the discrete version.

Bin Packing - How Do I Get My Stuff into the Boxes - Gehweiler, Joachim; Meyer auf der Heide, Friedhelm (Algorithms Unplugged)

Proceedings of the 23rd ACM symposium on Parallelism in algorithms and architectures - SPAA '11 - Rajaraman, Rajmohan; Meyer auf der Heide, Friedhelm

A survey on relay placement with runtime and approximation guarantees - Degener, Bastian; Fekete, Sándor P.; Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Computer Science Review)

Energy-efficient strategies for building short chains of mobile robots locally - Brandes, Philipp; Degener, Bastian; Kempkes, Barbara; Meyer auf der Heide, Friedhelm (SIROCCO '11: Proc. of the 18th International Colloquium on Structural Information and Communication Complexity)

A tight runtime bound for synchronous gathering of autonomous robots with limited visibility - Degener, Bastian; Kempkes, Barbara; Langner, Tobias; Meyer auf der Heide, Friedhelm; Pietrzyk, Peter; Wattenhofer, Roger (Proceedings of the 23rd ACM symposium on Parallelism in algorithms and architectures - SPAA '11)